Perception of Students on the Use of Google Classroom for Educational Purposes - Idoghor, Uduak; Oluwayimika, Kasumu Rebecca (Innovare Journal of Education, 2022)
This study investigated the Perception of students on the use of Google Classroom for educational purposes. Four research objectives, four research questions and three hypotheses guided the study. The population of the study used all education students in the Faculty of Education, University of Port Harcourt. A sample of 300 students was used for the study. Purposive and stratified random sampling techniques were used for the study and the instrument used to collect data was a structured questionnaire titled Perception of students on the use of Google Classroom in Tertiary Institutions (PSGCTI) with 40 items. A reliability coefficient of .74 was obtained for the structured questionnaire administered to students. Mean scores, Z-test and Anova, were used as the statistical tools for the study. It was found that the Google classroom platform helps students organize their assignments and it fosters better communication between teachers and students. It was also found that Google classroom makes online learning exciting and it creates creativity and critical thinking and makes students highly motivated. Based on the findings, it was recommended that Google classroom is a useful tool that every educator should use for teaching online. Furthermore, it was also recommended that teachers should use the Google classroom tool to bring about paperless communication in the classroom.